The therapeutic versatility of antihistamines: A comprehensive review. Issue 2 (February 2020) - Shirley, David W.; Sterrett, James; Haga, Neal; Durham, Catherine
Abstract : Abstract: Antihistamines are common and readily available medications for primary care patients and those seeking over-the-counter treatments. This article provides an overview of available antihistamines, their mechanisms of action, safety concerns in specific populations, and their therapeutic uses in several common conditions. Abstract : Antihistamines are common and readily available medications for primary care patients and those seeking over-the-counter treatments. This article provides an overview of available antihistamines, their mechanisms of action, safety concerns in specific populations, and their therapeutic uses in several common conditions.